A Fibroid or Cancer? A Rare Case of Mixed Choriocarcinoma and Epithelioid Trophoblastic Tumour. (2nd May 2013) - Luk, Wan Yu; Friedlander, Michael
Abstract : Background . Gestational trophoblastic disease (GTD) is a rare complication of pregnancy which is characterised by abnormal growth of the trophoblasts at the placental site. It is categorised into benign and malignant forms, which include hydatidiform moles (HMs) and gestational trophoblastic neoplasia (GTN), respectively. A mixed choriocarcinoma (CC) and epithelioid trophoblastic tumour (ETT) is an extremely rare subgroup of GTN, which is a highly curable but aggressive form of malignancy. Case . We report a case of mixed CC and ETT in a 41-year-old patient who presented with a 2-year history of menorrhagia and fibroid uterus in the absence of previous history of molar pregnancy. She had a 12-year interval between the antecedent pregnancy and presentation. She was treated with intensive regimen of adjuvant chemotherapy, etoposide, methotrexate, and actinomycin-D with etoposide and cisplatin (EMA-EP). She has remained disease free for more than 5 years. Conclusion . This case highlights the importance of considering GTN as one of the differential diagnoses value of β -HCG in patients presented with menorrhagia and growing fibroids.